Dynamic and thermodynamic modulations of the convectively coupled equatorial waves by the MJO. (17th March 2021) - Zhu, Yan; Li, Tim
Abstract: The convectively coupled equatorial waves (CCEWs), including the Kelvin, mixed-Rossby gravity (MRG), eastward inertio-gravity (EIG), and westward inertio-gravity (WIG) waves, are dominant synoptic-scale waves in the tropics. In this study, the modulation of the CCEWs by the MJO is examined with observational data from 1985–2005 over the Indian Ocean (IO), Maritime Continent (MC), and Western Pacific (WP). We find that the MRG wave is strengthened (weakened) to the west (east) of the MJO convection. In contrast, the Kelvin, WIG and EIG waves are mostly strengthened over the MJO convective center. As MJO modulates the background vertical wind shear and moisture fields, a further analysis was conducted to reveal the relationship between the background dynamic and thermodynamic field changes and the wave intensity change. A significant negative correlation between the MJO-scale vertical wind shear and the MRG intensity variation suggests that the MRG wave is primarily modulated by the dynamic field. The intensity changes of the WIG and EIG waves are significantly correlated to the MJO moisture field. The Kelvin wave, which has both quasi-geostrophic and gravity wave nature, is modulated by both the MJO-scale vertical wind shear and specific humidity.